Policy incentives and determinants of citizens' COVID-19 vaccination motives - Claudia Keser; Holger A. Rau (University of Göttingen, Department of Economics, 2022)
This paper presents the results of a survey exploring the determinants of vacinees' confidence in COVID-19 vaccines and their motivations to become vaccinated. At the threatening rise of the highly infectious Omicron variant, in December 2021, we interviewed people in waiting lines of vaccination centers. Our results identify risk-averse and social-distancing-compliant people as showing high confidence in the vaccine, which motivates them to receive it for reasons of protecting themselves and others. By contrast, policy incentives, such as "3G/2G" restrictions, motivate risktolerant people who opted for vaccination to get access to public areas. Trusting people who regularly vote are little afraid of vaccines' side effects. Our findings offer insights for policymakers in societies and firms that help to tailor policies promoting vaccination based on people's economic preferences
Keywords: C91; D81; H12; I12; I18; 330; Behavioral Economics; COVID-19; Policy Incentives; Vaccination Motives